2020
DOI: 10.1002/adfm.202004605
|View full text |Cite
|
Sign up to set email alerts
|

Polydiacetylene‐Based Biosensors for the Detection of Viruses and Related Biomolecules

Abstract: Viruses are a major threat to the wellbeing of humans, animals, and plants. The current diagnostics of viral RNA/DNA are largely dependent on polymerase chain reaction (PCR) and related concepts. Serological and immunological assays on the other hand aim to identify the presence of antibodies. Alternative approaches that consider non-biological entities as part of the sensing setup might be a complementary path to alleviate the pressure on access to high-quality biomolecules and PCR reagents. In this context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Charych et al (1993) first reported a PDA-based sensor that could detect hemagglutinin of the influenza virus [ 16 ]. Lately, PDA-based sensors have been reported to detect influenza virus, hepatitis B, foot-and-mouth virus, bovine viral diarrhea virus, feline calicivirus, and vaccinia virus [ 15 , 17 , 18 ], suggesting a potential of using PDAs as a colorimetric sensor for coronavirus detection [ 19 21 ]. To the best of our knowledge, no report has been published that describes a PDA-based colorimetric sensor to detect SARS-CoV-2.…”
mentioning
confidence: 99%
“…Charych et al (1993) first reported a PDA-based sensor that could detect hemagglutinin of the influenza virus [ 16 ]. Lately, PDA-based sensors have been reported to detect influenza virus, hepatitis B, foot-and-mouth virus, bovine viral diarrhea virus, feline calicivirus, and vaccinia virus [ 15 , 17 , 18 ], suggesting a potential of using PDAs as a colorimetric sensor for coronavirus detection [ 19 21 ]. To the best of our knowledge, no report has been published that describes a PDA-based colorimetric sensor to detect SARS-CoV-2.…”
mentioning
confidence: 99%
“…The same has also been con rmed by nisin which is known to interact with the cell membrane of target bacteria [47]. The bilayer-structured PDA vesicles in physiological environments can be easily obtained from the assembly of amphiphilic diacetylene monomers with phospholipids incorporated, which resemble the cellular membrane structure, making them ideal for bio-sensing purposes and for studying protein-membrane interactions [41]. In this membrane model the visible quanti able color changes were monitored in after peptide membrane interactions [48].…”
Section: Discussionmentioning
confidence: 79%
“…Further, the vesicles could be able to detect lower concentration of plantaricin LD1 in solution and resulted in an increase in color change and CR% indicating the sensitivity of the assay. The applications of PDA vesicles based sensors have also been explored in the other areas such as high-throughput screening of membrane acting antimicrobial peptides, pathogenic/food borne bacteria [11] and viruses (In uenza and latest coronavirus SARS-CoV-2) [41]. The authors have demonstrated great potential in providing a simple, low-cost, accurate and fastspeed detecting method alternative for the current methods which are too expensive and time-consuming for analyzing a large number of samples [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the outbreak of the pandemic virus such as severe acute respiratory syndrome coronavirus 2, securing a rapid but reliable and accurate identification of the causative pathogens became of crucial importance. [ 1–4 ] To date, a polymerase chain reaction (PCR)‐based genetic analysis is regarded as the most reliable gold standard diagnostic method due to its high accuracy and sensitivity toward the target biomarkers. [ 5,6 ] However, such a diagnostic method involves complex, laborsome steps of DNA extraction and harvest, amplification, and detection of the pathogen.…”
Section: Introductionmentioning
confidence: 99%